Competition between interatomic Coulombic decay and autoionization of doubly-excited atoms - Jabbari, Ghazal; Gokhberg, Kirill; Cederbaum, Lorenz S. (Chemical physics letters, 2020)
Doubly-excited atoms are known to autoionize. It is shown that in the presence of a neighboring atom, there is competition between autoionization and ICD (Interatomic Coulombic Decay) where the doubly-excited atom partially relaxes and the neighbor ionizes. Through a Rydberg series of doubly-excited states, the autoionization rate decreases in contrast to the ICD rate and ICD becomes dominant. Depending on the nature of the neighbor and the number of neighbors, other interatomic processes become operative even after autoionization, all demonstrating that the physics of doubly-excited species is strongly enriched in the presence of neighbors. Explicit examples are discussed.
Gesehen am 09.09.2020